ROS-Eliminating Carboxymethyl Chitosan Hydrogel to Enhance Burn Wound-Healing Efficacy - Yang, Cheng; Chen, Yuhui; Huang, Hai; Fan, Shicai; Yang, Chengliang; Wang, Liping; Li, Wenqiang; Niu, Wenxin; Liao, Jianwen (Frontiers in Pharmacology, 2021)
Over-expression of reactive oxygen species (ROS) can lead to chronic inflammation, which limits skin wound healing. Therefore, it is of great significance to develop materials that can locally control the adverse reactions caused by excessive ROS. In this research, an ROS-sensitive hydrogel with strong free radical scavenging ability was prepared by introducing the thione (Tk) group into carboxymethyl chitosan (CMCTS) hydrogel. CMCTS hydrogel was cross-linked by NH2-Tk-NH2 agent and loaded curcumin (Cur), which possessed favorable nontoxicity, water absorption, mechanical property, biodegradability, drug release behavior, the M2 phenotype, and inflammatory factor regulating the capacity of macrophages. It is worth noting that Cur@CMCTS-Tk hydrogel can significantly inhibit oxidative damage of human fibroblasts in the H2O2-induced microenvironment and protect their viability by reducing the production of intracellular ROS. In vivo, ROS-removing hydrogel effectively accelerated the process of wound healing and possessed good regenerative properties, including hair follicle formation, promotion of new blood vessel formation, and highly orderly arrangement of collagen fibers in the full-thickness skin burn defect rats model. Hence, we expect that the Cur@CMCTS-Tk hydrogel could be used for wound treatment and tissue regeneration due to the ability to scavenge excess ROS.